The Formulation Policy on Corporate Criminal Liability for Criminal Violations of Crimes against Biological Natural Resources and Ecosystems - Jazau Elvi Hasani (Universitas Nasional, 2019)
Indonesia is blessed with extraordinary natural wealth. Article 33 paragraph (3) of the 1945 Constitution stipulates that